A study on customer’s perception on logistic services by Multimodal Freight Sdn Bhd / Hartini Bt Abdul Halim - Abdul Halim, Hartini (2001)
Multimodal Freight Sdn Bhd (MMFSB) is a wholly subsidiary of Keretapi Tanah Melayu (KTM Berhad), the national railway company. Incorporated in 1988, the company was initially involved in freight forwarding activities mainly of KTM Bhd’s import rolling slocks, rails, spares and others. These activities were subsequently extended to other Malaysian exporters and importers for both air and sea shipments. Other transaction related activities such as container yard and warehousing services and road and vail transportation were brought on stream to cater to growing customer’s demand. In 1990, the Malaysian Government improved laden container haulage license and Multimodal Freight Sdn Bhd became one of the government approved container truckers in Peninsular. In addition, lately has been appointed as an approved Government Forwarder (Multimodal Transport Operator Kerajaan) to enable litem to undertake government procured shipment ex. Overseas. Today, Multimodal Freight Sdn Bhd (MMFSB) operates from eight locations nationwide and one in Singapore, offering customers a variety of Multimodal transportation and logistics services.